The Role of Leadership in Building an Effective Communication Culture at Al Hijrah IT Middle School 2 - Iman, Mujhirul; Aulia, Icha Natasya; Yasmin, Salsabila; Julia, Ayu Putri; Ubaidillah, Malik (Journal of Education and Teaching Learning, 2024)
This research aims to examine how the principal at Al Hijrah IT Middle School 2 develops and manages effective communication by exploring the strategies, approaches, and challenges faced. This study uses qualitative research methods with a descriptive approach. This method presents data as it is, without manipulation. Researchers used an interview guide with pre-arranged questions and explored in-depth information about the informants' experiences, perceptions, and motivations. Researchers also collected documents related to the research, such as field notes, photos, videos, artifacts, and official documents. Qualitative data analysis was conducted continuously during the data collection process. To ensure data validity, researchers used triangulation, a combination of data collection techniques (interviews, observations, and documentation) to obtain more complete and convergent information. This research was conducted at Al Hijrah IT Middle School 2, Kec. Percut Sei Tuan, Kab. Deli Serdang, with the subject being the principal of Al Hijrah IT Middle School 2. The urgency of an effective communication culture in education is crucial as it influences the success of the teaching and learning process. The research findings indicate that the principal of Al Hijrah IT Middle School 2 has implemented various strategies and approaches to strengthen an effective communication culture, significantly contributing to the performance and success of school programs.